Pengaruh Penambahan Abu Dasar (Bottom Ash) Sebagai Bahan Pengganti Pasir Pada Paving Block - Rezky Yusman Efendy; Zulfikar Djauhari; Ermiyati Ermiyati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This research aims to study the effect of bottom ash as substitute of sand in paving block and to classify each percentage of substitution according to SNI 03-0691-1906 Bata Beton (Paving Block) class specification. The mixture of cement and sand used in this study was 1 : 3. The variation of substitution started from 0%, 10%, 20%, 30%, 40% of sand weight. Tests performed on paving block include compressive strength, water absorption, Na2SO4 immersion test. The results shown by this research that water absorption test at substitution 0%, 10%, 20%, 30%, 40%, were 5.76%, 6%, 5.83%, 7.16%, 7.49%. According to SNI 030691-1906 “Bata Beton” (Paving Block) to water absorption test results, 0%, 10%, 20%, were categorized as B quality paving block, and 30%, 40% were categorized into C quality paving block. The results shown by this research that compressive strength test at substitution 0%, 10%, 20%, 30%, 40% were 31.80 MPa, 27.30 MPa, 29.61 MPa, 19.97 MPa, 16.41MPa. According to SNI 03-0691-1906 Bata Beton (Paving Block) to compressive strength test results, 0%, 10%, 20%, were categorized as B quality paving block, and 30%, 40%, were categorized into C quality paving block. Keywords: Paving Block, Bottom Ash, Water Absorption, Natrium Sulfate, and Compresive Strength